Comparison of the Effectiveness of Group Therapies based on Acceptance and Commitment and Schema on Coping Style Avoidance and Body Mass Index in Obese and Overweight People with Emotional Eating - Iman Najjar Kakhki; Maryam Kalhornia Golkar; Atefeh Nezhadmohammad Nameghi; Fatemeh Mohammadi Shirmahaleh; Majid Valizadeh (پژوهش‌های کاربردی روانشناختی, 2024)
The aim of this study was to compare the effectiveness of group therapies that were based on acceptance and commitment, as well as schema on coping-avoidance style, in individuals who were obese or overweight and were experiencing emotional eating. The present study was a quasi-experimental design that included a control group and a pretest-posttest. The research population included all men and women between the ages of 21 and 50 who visited nutrition and obesity clinics in Tehran during the summer and autumn of 2019. A sample of 60 individuals was randomly assigned to three groups of 20 individuals (acceptance and commitment therapy, schema treatment, and control) using the cluster sampling method and based on entry and exit criteria. The subjects completed the Dutch Eating Behavior Questionnaire (DEBQ) and the General and Exclusive Avoidance Questionnaire (GASQ) in three stages: pre-test, on-test, and post-test. The data were analyzed using SPSS version 24 software, which included covariance analysis and Bonferroni's post hoc test. The results indicated that group therapies based on acceptance and commitment and schema therapy were effective in reducing the avoidance of coping styles in obese and overweight individuals with emotional excess. The experimental groups exhibited a lower level of avoidance compared to the control group. The results suggest that overweight and obese individuals can decrease their reliance on coping style avoidance through group therapy that is based on acceptance, commitment, and schema therapy.